2016
DOI: 10.1037/lhb0000176
|View full text |Cite
|
Sign up to set email alerts
|

Boldness and its relation to psychopathic personality: Prototypicality analyses among forensic mental health, criminal justice, and layperson raters.

Abstract: Research on psychopathic personality has been dominated by a focus on criminality and social deviance, but some theoretical models argue that certain putatively adaptive features are important components of this construct. In 3 samples (forensic mental health practitioners, probation officers and a layperson community sample), we investigated adaptive traits as conceptualized in the Triarchic model of psychopathy (Patrick et al., 2009), specifically the relevance of boldness to construals of psychopathic perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Although past CAPP prototypicality research has demonstrated considerable overlap between mental health professionals and laypeople (Hoff et al, ), some differences have emerged between laypeople and mental health professionals. Only the latter group found moderate associations between boldness and CAPP Dominance (Sörman et al, ). Future research should explore similar lexical studies among mental health professionals to test whether conceptual confusion occurred among university students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although past CAPP prototypicality research has demonstrated considerable overlap between mental health professionals and laypeople (Hoff et al, ), some differences have emerged between laypeople and mental health professionals. Only the latter group found moderate associations between boldness and CAPP Dominance (Sörman et al, ). Future research should explore similar lexical studies among mental health professionals to test whether conceptual confusion occurred among university students.…”
Section: Discussionmentioning
confidence: 99%
“…Factor analyses of Comprehensive Assessment of Psychopathic Personality (CAPP; Cooke, Hart, Logan, & Michie, ) self‐ratings yielded a bi‐factor model comprising a Boldness/Emotional Stability residual factor (Sellbom, Cooke, & Hart, ). Further, laypeople have rated boldness as a relevant trait in Cleckley's () case studies (Crego & Widiger, ), and criminal justice and forensic mental health professionals have rated boldness as prototypical of psychopathy (Sörman et al, ). Taken together, some have argued that boldness is relevant to nomological networks and conceptualizations of psychopathy (Lilienfeld et al, ; Patrick, Venables, & Drislane, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the defining features of psychopathy proposed by Cleckley included multiple ostensibly adaptive characteristics, even going so far as to state that “everything about [the psychopath] is likely to suggest desirable and superior human qualities, a robust mental health” (, p. 339). Additionally, forensic and correctional professionals rate certain aspects of boldness (e.g., social dominance) as highly prototypical of the broader construct of psychopathy (Sörman et al, ), and boldness further appears to be relevant in distinguishing psychopathy from antisocial personality disorder (Murphy, Lilienfeld, Skeem, & Edens, ; Wall, Wygant, & Sellbom, ). The utility of boldness in this respect is reflected in the DSM‐5 alternative model of personality disorders (APA, ), which contains a psychopathy specifier for diagnoses of antisocial personality disorder to indicate the added presence of traits related to interpersonal dominance and emotional resiliency.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent research (Sörman et al, in press) indicates that criminal justice professionals (i.e., forensic mental health practitioners and probation officers) who work directly with offenders rate aspects of boldness as prototypical features of psychopathy and also associate boldness with quasi-adaptive behaviors (e.g., better social skills, avoiding arrest) and outcomes (e.g., life success).…”
mentioning
confidence: 99%